2010
DOI: 10.1021/es102948f
|View full text |Cite
|
Sign up to set email alerts
|

Formation of PCDD/Fs from the Copper Oxide-Mediated Pyrolysis and Oxidation of 1,2-Dichlorobenzene

Abstract: Formation of polychorinated dibenzo-p-dioxins (PCDDs) has been demonstrated to occur via surface-mediated reactions of chlorinated phenols. However, polychlorinated dibenzofurans (PCDFs) are observed in much lower yields in laboratory studies than in full-scale combustors where PCDFs are in higher concentrations than PCDDs. This has led to the suggestion that at least PCDFs are formed from elemental carbon in the de novo process. However, the potential for PCDF formation from reactions of chlorinated benzenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 62 publications
2
53
2
Order By: Relevance
“…According to our previous study, metals which vaporized as the particulate phase reacted with Cl to form chloride in flue gas (Chang et al, 2012). During this stage, metal chloride plays an important role in catalyzing the formation of PCDD/Fs (Lu et al, 2007;Nganai et al, 2011). Therefore, the PCDD/F content of ash increased with increasing Cl level in the input materials, which was also reported in a previous study (Hatanaka et al, 2005).…”
Section: Behaviors During Incineration Processsupporting
confidence: 70%
“…According to our previous study, metals which vaporized as the particulate phase reacted with Cl to form chloride in flue gas (Chang et al, 2012). During this stage, metal chloride plays an important role in catalyzing the formation of PCDD/Fs (Lu et al, 2007;Nganai et al, 2011). Therefore, the PCDD/F content of ash increased with increasing Cl level in the input materials, which was also reported in a previous study (Hatanaka et al, 2005).…”
Section: Behaviors During Incineration Processsupporting
confidence: 70%
“…The concentration of other transition metals falls within bounds typically found in fly ashes. From the perspective of PCDD/F formation, the concentration of copper in fly ashes is of importance, as copper is considered one of the most potent PCDD/F formation catalysts and has been studied extensively in the past 9, 19, 20, 40, 41 . The fly ash studied in here contains only 0.02 % Cu, which is within the range observed in fly ashes from waste incineration processes 3539 .…”
Section: Resultsmentioning
confidence: 99%
“…Reactions following the ‘precursor’ pathway involve a chlorinated aromatic molecule acting as a precursor to dioxin formation 1017 . Previous research on the mechanism for the surface-mediated formation of PCDD/Fs has confirmed the involvement of surface radicals bound to metal centers on the fly ash surface 8, 9, 18, 19 . Though the original mechanistic studies were performed over copper oxide clusters on silica, the mechanism applies to any surface center that can form surface radicals.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The concentration of CBz in flue gas of waste incinerator is much higher than dioxins, as well as 10-100 · that of CPh. The surfacemediated reactions of CBz is possibly a significant source of PCDD/F emissions (Nganai, et al, 2011), although the ratio of PCDFs to PCDDs is mostly more than 1.0. Considering the great correlation between CBz and PCDD/Fs, Ö berg and Bergstrom (1985) proposed CBz as a surrogate of PCDD/Fs.…”
Section: Introductionmentioning
confidence: 99%